EXPERIENCE OF APPLICATION MASTOPOL IN THE TREATMENT OF MASTOPATHY AND PREMENSTRUAL SYNDROME - A. G. Solopova; A. A. Safarov; A. D. Makatsariya (IRBIS LLC, 2016)
Recently there has been a great increase in the number of patients suffering from mastopathy, 30-70% in women of reproductive age, and the risk of changes in the mammary gland increases to 70% if a woman has any gynecological pathology. It is proved that in mastopathy cancers (including breast cancer) develop in 3-5 times often.The basic principles of treatment of fibrocystic mastopathy is the normalization of hormonal levels (ratio of sex hormones in a women's blood), elimination of stress and increase of the body's resistance to stressful situations. But homeopathy is not less important in the treatment of mastopathy. We have analysed the effectiveness of homeopathic Mastopol in the treatment of mastopathy, associated with mastalgia.